Effect of Navajivana Rasa with Pathyashadangam Kashaya Ghanasatwa in Classical Migraine - An Open Label Single Arm Pilot Study - Rohith.M.R; S.Thara Lakshmi; Kusumam Joseph (International Journal of Ayurveda and Pharma Research, 2021)
Migraine is the second most common cause of primary headache and as per GBD 2015; migraine was ranked third highest cause of disability worldwide. Migraine with aura is an episodic headache associated with certain features such as sensitivity to light, sound or movement; nausea, vomiting and various fully reversible neurological symptoms. The aim of study was to assess the effect of Navajivana rasa with Pathyashadangam kashaya ghanasatwa in Classical Migraine. The formulations were combined and made into a dispensable form of hard gelatin capsules. Selected participants were given with two 500mg capsules twice daily after food for 2 months and were observed during 1 month of follow up. Symptomatic features were assessed before treatment, after 2 months of medication & after follow up. The MIDAS score for the assessment of disability was assessed before and after 3 months of study period. The results showed that, the study drug was effective in relieving the sign & symptoms of classical migraine and in improving the quality of life.